2005
DOI: 10.1177/0149206304272151
|View full text |Cite
|
Sign up to set email alerts
|

Top Management Leadership and Influence on Innovation: The Role of Sociocultural Context

Abstract: This study proposes and tests a model for top-management influence on innovations. Three research questions are addressed: Is top managers’ influence on innovation a function of their leadership? Does socio-cultural context directly affect leadership? and, Does sociocultural context moderate the relationship of leadership with top-management influence on innovation? These questions are investigated with data from 12 European countries. The results show that leadership factors have strong effects on top-managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
265
1
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 307 publications
(304 citation statements)
references
References 46 publications
15
265
1
4
Order By: Relevance
“…The relationships between transformational leadership and workforce innovation (Elenkov & Manev, 2005;Gumusluog˘lu & Ilsev, 2009;Jung, et al, 2003;Morales, et al, 2006;Sarros, et al, 2008;Shin & Zhou, 2003;Sosik, et al, 2004), rewards and workforce innovation (Jong & Hartog, 2007;Walton, 2003;Yukl, 2002) and autonomy and empowerment and workforce innovation (Amabile, et al, 1996;George & Jones, 2008;Zhao, 2005) are consistent with previous studies. The lack of correlation between innovative supportive climate and workforce innovation is consistent with that of Gumusluog˘lu and Ilsev (2009) who found a negative www.ccsenet.org/ass Asian Social Science Vol.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The relationships between transformational leadership and workforce innovation (Elenkov & Manev, 2005;Gumusluog˘lu & Ilsev, 2009;Jung, et al, 2003;Morales, et al, 2006;Sarros, et al, 2008;Shin & Zhou, 2003;Sosik, et al, 2004), rewards and workforce innovation (Jong & Hartog, 2007;Walton, 2003;Yukl, 2002) and autonomy and empowerment and workforce innovation (Amabile, et al, 1996;George & Jones, 2008;Zhao, 2005) are consistent with previous studies. The lack of correlation between innovative supportive climate and workforce innovation is consistent with that of Gumusluog˘lu and Ilsev (2009) who found a negative www.ccsenet.org/ass Asian Social Science Vol.…”
Section: Discussionsupporting
confidence: 81%
“…After testing the theoretical model, they concluded that the linkage is positive and transformational leadership has a significant contribute to innovative climate in the organization. The findings of Sarros et al (2008) was consistent with findings of Shin et al (2003), García-Morales, Montes & Verdú-Jover (2006), Elenkov et al (2005) and Gumusluog˘lu and Ilsev (2009). Based on the prominent role of the leader in the development of innovative workforces, Hypothesis 1 is one of the important hypotheses:…”
Section: Transformational Leadership and Workforce Innovation And Persupporting
confidence: 85%
See 2 more Smart Citations
“…However, firms' socio-cultural environment, which includes norms, customs and institutions, can also influence industry, business and organisational culture. Since innovation requires learning new ways of doing things, which also necessarily involves a continuous process of unlearning and forgetting old ways of doing thing (Senge 1990), culture can therefore significantly affect firms' propensity to innovate as well as their innovation success (Elenkov and Manev, 2005;Simmie, 2004;Ansoff, 1979;Drucker, 1998, Senge, 1990. In this respect, the construction industry is viewed as particularly conservative, with low innovation rates (Winch, 1998;Bregulla et al, 2003;Taylor and Lewitt, 2004;Widén, 2006;Visscher & Meijer, 2007).…”
Section: Methods and Techniquesmentioning
confidence: 99%